Understanding and eliminating thermo-mechanically induced radial cracks in fully metallized through-glass via (TGV) substrates. (May 2021) - Okoro, Chukwudi; Jayaraman, Shrisudersan; Pollard, Scott
Abstract: This work aims to understand and eliminate the formation of thermo-mechanically induced radial cracks in copper (Cu) metallized through-glass via (TGV) substrates made of Corning® high purity fused silica (HPFS® fused silica), after subjection to 420 °C annealing treatment. Radial cracks were found to be formed in Cu TGV substrate during the heating step of annealing treatment process, caused by high stress buildup resulting from the large mismatch in the coefficient of thermal expansion (CTE) between the HPFS® fused silica substrate and the Cu metallization. From analytical studies, high tensile circumferential stresses were found to be the main stress component that is responsible for the formation of radial cracks during heating. From experimental studies, it was found that radial crack formation was exponentially dependent on the applied heating rate, and that faster heating rate increased the probability for their formation. However, a crack-free metallized TGV substrate was achieved when heating rates ≤6.5 °C/min was applied, thus, eliminating radial crack formation. Radial crack elimination was attributed to the significant activation of stress relaxation mechanisms in the Cu. This was confirmed by the measurement of an inverse dependence of Cu protrusion with the applied heating rate. Additionally, the Cu protrusion data confirms that the leading stress relaxation mechanisms in the Cu TGV were grain boundary sliding (GBS), plastic deformation and Coble diffusional creep. Highlights: This work studies the impact of heating rate on the formation of thermo-mechanically driven radial cracks in Cu through-glass via (TGV) substrate. Radial crack formation was found to exponentially scale with increasing annealing heating rate. Elimination of radial cracks in Cu TGV substrate was achieved when an annealing heating rate of ≤ 6.5°C/min was used.